On deconstruction theory and criticism after structuralism - Culler, Jonathan D. (Cornell University Press, 1982)
With an emphasis on readers and reading, the author considers deconstruction in terms of the questions raised by psychoanalytic, feminist, and reader-response criticism. As a result, this book is both an authoritative synthesis of Derrida's thought and an analysis of the often-problematic relation between his philosophical writings and the work of literary critics.